2016
DOI: 10.1016/j.ijscr.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Primary retroperitoneal Merkel cell carcinoma: Case report and literature review

Abstract: HighlightsThere are only two cases reported in the literature Merkel cell carcinoma in the retroperitoneum.The most plausible theory is the retroperitoneal mass could be a massively enlarged lymph node where precursor cells became neoplastic.The less probable theory is the non-described “regression” phenomena of a cutaneous MCC, but we are not found a primary skin lesion.Preoperative chemotherapy and excision of the primary tumor is the surgical treatment of choice for retroperitoneal MCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Clinically the MCC appears typically like primary a cutaneous injury (75%), although it can make debut as a metastatic disease [7]. There are currently two possible explanations for what occurred in our patient.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Clinically the MCC appears typically like primary a cutaneous injury (75%), although it can make debut as a metastatic disease [7]. There are currently two possible explanations for what occurred in our patient.…”
Section: Discussionmentioning
confidence: 74%
“…In the presence of a nodal Merkel cell tumor, an exhaustive clinico-radiologic search for a primary tumor must be carried out [7]. MRI of abdomen, pelvis and thighs is realized and Fibro colonoscopy was made in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Siref et al reported a case of MCC presenting as a visceral malignancy where there were no cutaneous findings [19]. Quiroz-Sandoval et al reported a case of large retroperitoneal mass presenting as MCC, which was successfully excised [20]. As for our patient, she had neither personal nor family history of malignancy and presented with acute respiratory failure in the setting of pleural effusion with hilar mass and liver mass.…”
Section: Table 1: Immunobiological Markers Of MCCmentioning
confidence: 73%
“…Only 13 cases [5][6][7][8][9][10][11][12][13][14][15][16][17] met the condition of having a retroperitoneal Merkel cell involvement without primary skin lesion, they are summarized in Table 1. Most of the cases had retroperitoneal nodal affection (7 cases) or pancreatic involvement (2 cases), with only 4 plus our case with a real retroperitoneal mass of unknown origin that could be classified as the main tumor [5][6][7][8].…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…Most of the cases had retroperitoneal nodal affection (7 cases) or pancreatic involvement (2 cases), with only 4 plus our case with a real retroperitoneal mass of unknown origin that could be classified as the main tumor [5][6][7][8].…”
Section: Literature Review Resultsmentioning
confidence: 99%